Abstract 017: Rapid Progression Of Microhemorrhage In A Patient With An Atypical CADASIL Variant - Mohammad R Ghani; Eric Roddy; Wei Liu; Martin Brown (Stroke: Vascular and Interventional Neurology, 2023)
Introduction CADASIL (cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy) is a rare inherited disorder in which thickening occurs in the walls of small and medium‐sized blood vessels, which results in decreased cerebral blood delivery. CADASIL is most often established as a diagnosis with identification of a heterozygous pathogenic variant of the NOTCH3 gene by way of molecular genetic testing. In this abstract we identify an atypical presentation of CADASIL with a heterozygous pathologic variant of the HTRA1 gene. This case is unusual in its late onset, as the disease typically presents in the third to fourth decade of life. Additionally, the prevalence of microbleeds in CADASIL typically correlates with patient age. Methods Electronic charts of a patient with recurrent strokes and positive genetic testing were reviewed. Results A 63‐year‐old right‐handed African American male with hypertension, hyperlipidemia, diabetes mellitus, and a history of cerebrovascular disease and cervical myelopathy initially presenting in 2020 lower extremity weakness and progressive apraxia of speech. He had a documented history of transient‐ischemic attack and was noted to have undergone progressive cognitive decline. His presentation raised concern for etiology such as vasculitis or multiple sclerosis and prompted a genetic workup, which was obtained on outpatient follow‐up. The patient presented several more times emergently with similar symptoms that included the reoccurrence and progression of his spastic lower extremity weakness as well as the development of a pseudo‐bulbar affect. Initial MRI brain demonstrated areas of DWI hyperintensity scattered throughout the bilateral hemispheres without ADC correlation. Post‐contrast T2 sequencing demonstrated hyperintensities in the callosal splenium and left centrum semiovale. Genetic testing consisting of Hereditary Cerebral Small Vessel Disease and Hereditary Spastic Paraplegia panels through Invitae were obtained. The first panel evaluates 10 genes for variants which are associated with hereditary forms of cerebral small vessel disease, encompassing those conditions in which small arteries, arterioles, venules, and capillaries of the brain are compromised. The Hereditary Cerebral Small Vessel Disease genetic panel resulted in the positive identification of a likely‐pathogenic variant of the HTRA1 gene, which is associated with CADASIL 2. The Hereditary Spastic Paraplegia genetic panel was unremarkable, as were CSF studies obtained for evaluation of a demyelinating or inflammatory cause. Repeat MRI obtained twice more over the patient’s repeated presentations and demonstrated a large interval increase in areas of low‐signal gradient echo over the course of approximately three months, which represented an evolution in the number of microhemorrhages beyond what would be expected in such a short period of time. Conclusion Scientific literature describes the prevalence of microhemorrhages in CADASIL to be somewhere between 38‐75%. However, there have been few studies which detail such a rapid progression of microhemorrhages in this patient population as well as such a late progression of the disease. Our case demonstrates a unique presentation of CADASIL and provides a remarkable example of rapid, late‐in‐life disease presentation. Further research is needed to elucidate and characterize disease leading to early diagnosis and management.